BENTUK DAN MAKNA MEME BERBAHASA ARAB DALAM MEDIA SOSIAL INSTAGRAM SHUWARUN MUDHCHIKATUN - Astarini Arlita Sari, Arifuddin (Center of Middle Eastern Studies (CMES): Jurnal Studi Timur Tengah, 2017)
This paper examines the forms of Arabic meme based on lingual and visual aspect and meaning of rage face in social media InstagramShuwarun Mudhchikatun. The data used in this paper are taken from social media InstagramShuwarun Mudhchikatun in the period June - July 2015. This research applied qualitative research methods which divided into three steps. First, collecting data through observation method with uninvolved conversation observation technique and noting technique. Second, analyzing data by distribution method with direct segmenting constituents technique and taxonomy technique. Third, presenting data by informal technique. This research concludes that the forms of Arabic meme in social media InstagramShuwarun Mudhchikatunbased is divided to lingual and visual aspect. The lingual aspect consists of word, phrase, clause, and sentence. In addition, form of combination grammatical units such as word and phrase, phrase and word, phrase and clause, and phrase and sentence. Form of Arabic meme based on the visual aspect found consist of icon, icon and index, icon and symbol, and icon, index, and symbol. As for the meaning of rage face in social media InstagramShuwarun Mudhchikatunconsistof five meaning. They arejoy, sadness, anger, surprise and neutral.